Expression and function of purinergic P2Y12 receptors in rat trigeminal ganglion neurons. (September 2015) - Kawaguchi, Aya; Sato, Masaki; Kimura, Maki; Ichinohe, Tatsuya; Tazaki, Masakazu; Shibukawa, Yoshiyuki
Highlights: Expression of P2Y12 receptors in TG neurons remains to be fully elucidated. We showed expression/function of P2Y12 receptors in the TG neurons. Activation of P2Y12 receptors in the TG neurons couples with cAMP-dependent pathway. P2Y12 receptors activate cAMP-dependent mobilization of intracellular Ca 2+ . Abstract: Purinergic receptors play key signaling roles in neuropathic pain in the orofacial region, which is innervated by trigeminal ganglion (TG) neurons. The neuropathology of purinergic P2Y12 receptors is well characterized in glia; however, their physiological role in TG neurons remains to be fully elucidated. The present study investigated the expression and function of P2Y12 receptors in rat TG neurons. P2Y12 receptor immunoreactivity was intense in the soma, dendrites, and axons, and colocalized with a pan-neuronal marker, neurofilament H, isolectin B4, and substance P. In the presence of extracellular Ca 2+, 2-methylthio-ADP (an agonist of P2Y1, 12, 13 receptors) transiently increased intracellular free Ca 2+ concentrations ([Ca 2+ ]i ), an effect that was abolished by P2Y12 receptor antagonists. In the absence of extracellular Ca 2+, ryanodine receptor/channel inhibitors diminished the 2-methylthio-ADP-induced increases in [Ca 2+ ]i . A sarcoplasmic reticulum Ca 2+ -ATPase (SERCA) inhibitor gradually increased [Ca 2+ ]i, and after a plateau, application of 2-MeS-ADP induced a rapid and transient, but additive increase in [Ca 2+ ]i . An adenylate cyclase inhibitor transiently increased [Ca 2+ ]i, while a phosphodiesterase inhibitor prevented the 2-methylthio-ADP-induced increase in [Ca 2+ ]i . Our study shows that P2Y12 receptors are expressed in TG neurons, and act via a cAMP-dependent pathway to release intracellular Ca 2+ from ryanodine-sensitive Ca 2+ stores.